Tribo-Electrochemical Considerations for Assessing Galvanic Corrosion Characteristics of Metals in Chemical Mechanical Planarization - Kassapa U. Gamagedara; Dipankar Roy (Electrochem, 2025)
The manufacturing of integrated circuits involves multiple steps of chemical mechanical planarization (CMP) involving different materials. Mitigating CMP-induced defects is a main requirement of all CMP schemes. In this context, controlling galvanic corrosion is a particularly challenging task for planarizing device structures involving contact regions of different metals with dissimilar levels of corrosivity. Since galvanic corrosion occurs in the reactive environment of CMP slurries, an essential aspect of slurry engineering for metal CMP is to control the surface chemistries responsible for these bimetallic effects. Using a CMP system based on copper and cobalt (used in interconnects for wiring and blocking copper diffusion, respectively), the present work explores certain theoretical and experimental aspects of evaluating and controlling galvanic corrosion in barrier CMP. The limitations of conventional electrochemical tests for studying CMP-related galvanic corrosion are examined, and a tribo-electrochemical method for investigating these systems is demonstrated. Alkaline CMP slurries based on sodium percarbonate are used to planarize both Co and Cu samples. Galvanic corrosion of Co is controlled by using the metal-selective complex forming functions of malonic acid at the Co and Cu sample surfaces. A commonly used corrosion inhibitor, benzotriazole, is employed to further reduce the galvanic effects.